Determinação da atividade antiglicante de extratos de plantas sobre produtos de glicação avançada (AGE) in vitro - Melo, Ingrid Sofia Vieira de (2015)
Advanced glycation end products the (AGE) comprise a series of compounds, quite different, whose activity is related to their ability to modify the chemical and functional properties of diverse biological structures. Several studies, including that used animals, indicate that AGE restriction in the diet can have many protective effects. Furthermore, the use of certain medicinal plants appears to offer additional benefits, especially to individuals suffering from disorders associated with excessive accumulation of AGE. It is believed that plants combiam antiglicantes and antioxidant properties, have positive effects on the inhibition of glycation. This fact has attracted the interest of the scientific community, as it can provide important therapeutic potential. Although any further component is particularly suitable as reducing AGEs in the context of the human body, some substances in vitro studies demonstrated the anti-AGE effects important and worth further investigation such as pyridoxamine, alilcisteína (garlic extract component), phenolics, vitamins C and E, thiamin, taurine and carnosine, recognized for its antioxidant properties. Therefore the aim of this proposal was to determine the antiglicante activity of extracts of plants native to the brasileleira flora of recognized antioxidant activity. All the studied extracts are part of the bank of plant extracts belonging to the Laboratory for Research on Natural Resources (LPqRN), the Institute of Chemistry and Biotechnology - UFAL. Therefore, this thesis was divided into three parts, which generated three articles. The first titled "Antioxidant activity of native plant extracts of flora by ABTS methods, DPPH, FRAP and ORAC", aimed to investigate the antioxidant capacity of different plant extracts, by different in vitro assays (ABTS, DPPH, FRAP , ORAC), and determine whether there is correlation between the tested methods. In this proposal, 49 plant samples were studied, the tests of antioxidant capacity, DPPH; ABTS; FRAP and ORAC. Further tests were conducted to see if there was a correlation between the methods. The results were screened for to follow up the research, specifically, the antiglicante activity, believed to be related to the antioxidant activity. So the second article entitled "antiglicante in vitro activity of native plant extracts of flora", aimed to determine the antiglicante activity of native plant extracts of brazilian flora, with recognized antioxidant activity and the possibility of correlation between tests, antiglicante and antioxidants. For this 18 extracts, which had been classified as important sources of antioxidant compounds were tested for activity antiglicante. From the most promising extract, Auxemma oncocalyx Taub. (Bark) for activity, an isolated quinone thereof was tested in Oncocalixona A. This may be an important antiglicante agent, which resulted in the third section, "Oncocalyxone The functions of an anti-glycation agent in vitro", that this was submitted to the journal FOOD CHEMISTRY, ISSN: 0308-8146, Impact factor 3.259, on 02/12/14, in the form of Short communication. The particular this thesis is of importance, since investigations of this nature favors the development of research investigating potential therapeutic products, and that in turn may be useful in treating diseases associated with excessive accumulation of AGE